EVALUATION OF MICROBIAL FLOC AND MICROALGAE Spirulina platensis COMBINATION FOR JUVENILE COBIA Rachycentron canadum DIETS ON GROWTH AND PHYSIOLOGICAL RESPONSES AFTER IMMERSION IN FRESHWATER - Suryadi Saputra; Muhammad Agus Suprayudi; Enang Harris; Mia Setiawati; . Widanarni; Suci antoro (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2016)
In marine aquaculture, immersing marine fish species in fresh water can remove ectoparasite that adhere to all over the fish body. This study aimed to evaluate the impacts of combining microbial floc and microalgae Spirulina platensis in juvenile cobia diet on growth performance and stress responses after immersion in aerated fresh water for 15 minutes. The fishes were reared in concrete tanks for 40 days before collecting data on their growth performance. The stress response was determined by mea-suring both glucose and cortisol levels before (0 h) and after (1, 2, 4, 6, 24 hours) immersion. The fish-es fed on the 15% of combining microbial flock and microalgae Spirulina platensis diet showed the highest growth rate with the lowest feed conversion ratio compared to other treatments. The cortisol level of juvenile cobia in both the 15% and 30% combination of microbial floc and microalgae Spiru-lina platensis treatments did not increase during the first hour following the immersion compared to the control treatment. The glucose level also increased after one hour immersion in freshwater of all treatments. This indicated that feeding juvenile cobia on microbial flocs and microalgae diets had a retarding effect on the physiological responses (cortisol and glucose) after immersion in fresh water.Keywords: microbial, microalga, Spirulina, glucose, cortisol, stress, cobia